Pneumoascariasis: Ascaris Worm Infestation in the Lungs - Widiastara, Antonio Ayrton; Ferreira, Esmeraldito; Basuki, Sukmawati (Faculty of Medicine Universitas Airlangga, 2024)
Pneumoascariasis is an infestation from one of the most common worms or helminths found on earth in the respiratory system. The worm is called Ascaris lumbricoides, which penetrates and infests the human body through the fecal-oral process. The fertilized Ascaris ova, or simply egg, would develop into larvae, which then move to the liver and lungs through the portal vein system. These larvae will soon develop into mature worms in the human respiratory system, inside the lungs, particularly in the bronchioles. These Ascaris larvae trigger common symptoms such as persistent cough, shortness of breath, and wheezing. To diagnose this condition, supplementary examinations are necessary since it is difficult to diagnose only by history taking and some physical exams. Additional exams include chest X-rays that, at one point, display lung infiltration. The chest computed tomography (CT) scan shows ground-glass opacity and a classic inflammation marker called Charcot-Leyden crystals that are most likely present. Pneumoascariasis is often misinterpreted and misdiagnosed. Therefore, this literature review was made to further understand about pneumoascariasis.